An interdisciplinary corpus-based analysis of the translation of كرامة (karāma, 'dignity') and its collocates in Arabic-English constitutions - Claire Brierley; Hanem El-Farahaty (JoSTrans: The Journal of Specialised Translation)
We examine whether occurrences of the human rights term كرامة (karāma, 'dignity') in the Leeds Parallel Corpus of Arabic-English Constitutions imply a shared understanding of this term from source to target text. Our approach combines quantitative and qualitative techniques from corpus linguistics and Arabic legal translation and contributes to theory and practice in computer-assisted legal linguistics and translation. Our methodology includes: specification of morphological variants of كرامة ; scrutiny of parallel concordance lines; and analysis of the semantic prosody of target terms via their collocations. We identify 65 instances (or variants) of كرامة in the Arabic data: its raw frequency is highest in the constitutions of Egypt and Sudan but missing in that of Palestine. We find that while the indefinite noun كرامة is always translated as 'dignity', the definite form (الكرامة , al-karāma) is often rendered as 'treatment' plus a qualifying adjective. The combination of كرامة and negation results in qualification of 'treatment' with notions of humiliation and cruelty, as evidenced via collocation discovery over both sub-corpora of 19 constitutions. This suggests a common understanding of كرامة and dignity as an inviolable human right across these different languages and cultures, fostered perhaps by the theological significance of these terms.